New name to reflect change in emphasis from agriculture to science, UPM now Universiti Putra Malaysia - New Straits Times, Tengku Sariffuddin (1997)
SERDANG, Thurs. - Universiti Pertanian Malaysia has been renamed Universiti Putra Malaysia from today to reflect the change in the emphasis from agriculture to science programmes. Prime Minister Datuk Seri Dr Mahathir Mohamad who made the announcement during a one-day visit to UPM, said the new name was appropriate since the university's academic programmes were no longer confined to agriculture. Putra also reflected the increasing abilities of Malaysian youths, he said when addressing some 3,000 staff and UPM students who had packed the university's Sultan Salahuddin Abdul Aziz Shah culture and arts centre. Dr Mahathir's announcement was met with strong approval from the crowd who gave him a standing ovation while UPM vice-chancellor Professor Datuk Syed Jalaludin Syed Salim shook hands with him. UPM was formed in 1971 by merging College of Agriculture Malaya in Serdang with the Faculty of Agriculture, University Malaya. It now has 10 faculties offering 24 degree programmes, nine diploma programmes and seven graduate studies programmes at Masters and doctoral levels and a student population of 14,000. Dr Mahathir said the Government had picked the name because UPM was situated near Putrajaya, the new administrative capital within the Multimedia Super Corridor. He also said it was in honour of Malaysia's first Prime Minister Tuanku Abdul Rahman Putra. "We hope the change in name will serve to motivate the students to study hard to serve the aspirations of our race and nation. "It is alright to seek wealth but we all have a responsbility to make Malaysia a country which is respected by others." Dr Mahathir had a busy schedule during the one-day visit, He was given a briefing by Syed Jalaludin and witnessed the signing of a memorandum of understanding between UPM and TR Group of Companies to set up the Malaysian Graduate School of Management. He then addressed the students and launched UPM On-Line and UPM Net. After lunch, Dr Mahathir launched the UPM-MTDC Technology Incubation Centre One where he spent almost three hours visiting information technology-related companies. Lastly, he launched Time Telekom's RM30 million Earth Station which serves UPM-MTDC telecommunication needs and Time's customers nationwide. Dr Mahathir said UPM was playing a vital role in scientific and technological research and development such especially in information technology. "Today we see tremendous progress being made and the knowledge gained has contributed to the creation of several products and unique production methods not developed by other parties," he said. He said although UPM was placing greater emphasis on science subjects it would not neglect agricultural programmes as the development of that sector was still important to the Government. Research and development in agriculture would continue as the country needs to boost productivity in that sector. Dr Mahathir said Malaysians had the ability to acquire knowledge in all fields including science which was essential for the nation to progress and become a developed nation. "We need to have concentration to acquire the knowledge ... and we should not do this just out of self-interest. "We have a reponsibility to contribute toward making Malaysia a great nation," he said. During the dialogue, with the students, Dr Mahathir assured them that the Government would provide financial assistance to poor students once universities were corporatised. The move would allow the universities to source additional financial assistance and would help check the brain drain. Dr Mahathir said the Government could not raise the wages of academic staff substantially to check the brain drain without doing the same for other civil servants. "With corporatisation, academics will get higher wages. We are thankful to them for remaining with the universities even though they can earn higher wages in the private sector." On social ills, Dr Mahathir said the Government was conducting a study to ensure measures taken to check them were effective.